Development of a microcontroller-based control system with a hardware-in-the-loop (HIL) method for control education using MATLAB/Simulink/xPC target - Martono, Wahyudi; Salami, Momoh Jimoh Emiyoka; Albagul, Abdulgani (Tempus Publications, 2005)
This paper discusses the development of control systems with hardware-in-the-loop simulation (HILS) method for enhancing the teaching of control engineering. Two control systems based on the HILS approach were developed namely simulated plant HILS (SP-HILS) and simulated controller HILS (SC-HILS) control systems. The SP-HILS control system uses an actual hardware of the controller and the plant is simulated in the computer based on its dynamic model. On the other hand, in the SC-HILS control system, the real/actual plant is used but the controller is simulated on the computer. In general these proposed systems consist of both hardware and software. The software tools of MATLAB/Simulink/xPC Target by MathWorks, Inc and a C++ compiler are used to simulate the physical system (plant) to be controlled and used to simulate the controller in the SP-HILS and SC-HILS systems respectively. The hardware of the SP-HILS includes a microcontroller as a controller and interfacing circuits to allow communication between the simulated plant and the real controller, while the SC-HILS uses a lab-scale gantry crane including its sensors for feedback. The proposed systems are inexpensive and allow students to carry out extensive experimental investigation as well as the design, implementation, performance evaluation and comparative studies of controllers. A case study of the controller design and implementation for an active suspension system in the SP-HILS and PID controller design and implementation for automatic gantry crane in the SC-HILS are presented to illustrate the application of the proposed systems.